Development and Characterization of a New Endoscopic Drug-Eluting Platform With Proven Efficacy in Acute and Chronic Experimental Colitis - Bon, Ignacio; Cano-Sarabia, Mary; de la Ossa, Napoleon; Bartolí, Ramon; Lorenzo-Zúñiga, Vicente (Frontiers in Medicine, 2020)
Background and Aims: Mucosal lesions refractory to biological treatments represent unmet needs in patients with inflammatory bowel disease (IBD) that require new treatment modalities. We developed and characterized a new endoscopic drug-eluting hydrogel (CoverGel) with proven efficacy in acute and chronic experimental colitis (EC) in rats. Methods: CoverGel was developed based on appropriate rheological, drug release, gelation, structural, and degradation property capacities to allow endoscopic application. Experimental colitis (EC) was induced by TNBS application in rats. In acute EC 40, rats were randomized in five groups (eight each): Sham, Control, CoverGel, CoverGel + Infliximab (IFX) and CoverGel + Vedolizumab (VDZ). In chronic EC, 12 rats were randomized in two groups (six each): IFX s.c. and CoverGel + IFX. Endoscopic, histological, and blood test were performed during follow-up to evaluate clinical success. Antibodies to IFX (ATIs) were evaluated in chronic EC animal study. Results: CoverGel is a biocompatible and bioadhesive reverse thermosensitive gelation hydrogel with a macroporous structure and drug release capacity. In acute EC animals treated with CoverGel + IFX or CoverGel + VDZ showed significantly clinical success (weight recovery, mucosal restoration, and bacterial translocation) as compared with controls and animals without a bioactive drug. In a chronic EC animal study, clinical efficacy was comparable in both groups. Levels of ATIs were significantly lower in animals treated with CoverGel + IFX vs. IFX s.c. (0.90 ± 0.06 μg/mL-c vs. 1.97 ± 0.66 μg/mL-c, p = 0.0025). Conclusions: CoverGel is an endoscopic vehicle to locally deliver biological drugs with proven efficacy in acute and chronic EC in rats and induce less immunogenicity reaction.